2021
DOI: 10.1088/1361-6463/ac18ec
|View full text |Cite
|
Sign up to set email alerts
|

Following O and OH in He/O2 and He/H2O gas mixtures—from the gas phase through the liquid phase to modifications on a biological sample

Abstract: Applied cold atmospheric plasma allows for the controlled delivery of reactive oxygen and nitrogen species tailored for specific applications. Through the manipulation of the plasma parameters, feed gases, and careful consideration of the environment surrounding the treatment target, selective chemistries that preferentially influence the target can be produced and delivered. To demonstrate this, the COST reference microscale atmospheric pressure plasma jet is used to study the generation and transport of O an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
(138 reference statements)
0
13
1
Order By: Relevance
“…[34] Here, the He/H 2 O admixture was selected based on the extensive characterization of the gas and liquid phase performed in previous experiments. [30,35,36] To limit the effect of impurities in the discharge, gas delivery was regulated via stainless steel tubing. As a reference jet, the COST-Jet is well studied and previous research has reported its reproducibility, [37] gas-phase densities of reactive species, [34,36,38,39] and liquid phase densities, [30,35,[40][41][42] among others.…”
Section: Plasma Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…[34] Here, the He/H 2 O admixture was selected based on the extensive characterization of the gas and liquid phase performed in previous experiments. [30,35,36] To limit the effect of impurities in the discharge, gas delivery was regulated via stainless steel tubing. As a reference jet, the COST-Jet is well studied and previous research has reported its reproducibility, [37] gas-phase densities of reactive species, [34,36,38,39] and liquid phase densities, [30,35,[40][41][42] among others.…”
Section: Plasma Setupmentioning
confidence: 99%
“…[30,35,36] To limit the effect of impurities in the discharge, gas delivery was regulated via stainless steel tubing. As a reference jet, the COST-Jet is well studied and previous research has reported its reproducibility, [37] gas-phase densities of reactive species, [34,36,38,39] and liquid phase densities, [30,35,[40][41][42] among others. The nozzle of the COST-Jet was placed 4 mm above the liquid surface, see Figure 1.…”
Section: Plasma Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The O atoms can survive contact with the water surface, dissolve into the liquid, and react in the liquid phase with dissolved species. [31,32] Oxidations of chloride anions, [33][34][35][36] phenol, [30,31,33] glucose, [37] amino acids (AAs), and peptides [38][39][40] were reported. Among other processes, the reactions of ROS in chloride solutions are of great importance because the Cl − ions are inherently present in biological tissue, the cellular environment, culture media, and physiological solutions (0.9%).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the thiol-group containing AAs oxidized by plasma were shown to be responsible for the cytotoxic activity of plasma-treated cell culture media. [39,[42][43][44][45] A comprehensive study was performed on mixtures of AAs and simple peptides treated by an Ar plasma jet with an admixture of O 2 / N 2 . [38] Oxidation, nitration, and chlorination of AAs depended upon the type of discharge feed gas.…”
Section: Introductionmentioning
confidence: 99%